Quadrature And Cubatura Formulas for Calculation of Exact Integrals (Eurasian Journal of Humanities and Social Sciences, 2021)
The article presents the basic quadrature and cubature formulas used to calculate definite integrals. Quadratic formulas are relatively simple, therefore, theoretical information about them is given. Since the cubature formulas are a little more complicated than the quadrature formulas, the calculation of definite integrals using the same formulas is shown and their degree of accuracy is compared. Simpson’s method has been shown to give relatively accurate results.